Stress-Driven Spending: Correlates of International Students’ Adjustment Strains and Compulsive Online Buying - Lou, Yana; Byun, Sang-Eun (Journal of International Students, 2018)
We investigated international students’ stress-driven spending behavior by focusing on the psychological and behavioral consequences of the strains they experience during the adjustment process in the U.S. We found that certain adjustment strains significantly lowered international students’ self esteem, which further affected their happiness and engagement in compulsive online buying. This study highlights the importance of understanding underlying drivers and consequences of international students’ adjustment strains to facilitate better adaptation to a foreign culture and to prevent negative consumption tendencies.